The Role of Infectious Inflammatory Processes in the Bronchial Asthma Pathogenesis in Children - O.Ye. Chernyshova (Zaslavsky O.Yu., 2014)
The article describes the impact of intracellular pathogens on the formation of airways inflammation in asthmatic children.